Public Debt and Agricultural Sector Performance in Nigeria - Lewis Dormaa GBARAYORKS (World Journal of Entrepreneurial Development Studies, 2026)
This study examined public debt and agricultural sector performance in Nigeria for the period 1981-2022. The public debt variables included external debt, domestic debt, total debt and debt servicing. These constituted the specific objectives of the study. Agricultural sector performance was proxied with agricultural GDP. Data were sourced from the CBN Statistical Bulletin and analyzed using error correction model. The result indicated that domestic debt and total debt have positive and significant effects on agricultural sector output while external debt and debt servicing exerted a significantly negative effect on agricultural sector output in Nigeria. The study determined that foreign debt has had a major negative impact on the expansion of Nigeria's agricultural industry, owing to the overbearing effect of debt payment, which also reduces sector production. Domestic debt has had a relatively minor impact on the agriculture industry. It was suggested that the government directly support the agriculture sector through domestic borrowings and explicitly fund the sector with foreign borrowings designated for the agricultural industry. By doing this, loan service may be done directly from the earnings of agricultural produce, which increases agricultural productivity in Nigeria in the long term.